The Collectivization of Agriculture in Communist Eastern Europe - Constantin Iordachi, Arnd BauerkÃ¤mper (Central European University Press, 2014)
The sweeping economic and sociopolitical changes set into motion by the collapse of communist dictatorships and the end of the Cold War have significantly transformed Eastern European societies. In the last two decades, numerous scholars in various disciplines have attempted to understand the nature of these changes and assess the societal impact of Eastern European integration into European and Euro-Atlantic security and sociopolitical organizations. These research efforts have mostly focused on the transformation of legal-political systems, on mechanisms of elite (re)production, and on processes of privatization and restructuring of property relations. Much less attention has been devoted to changes in rural transformation areas, despite the fact that the peasantry continues to be an important segment of the population in all countries in the region. Moreover, when attention has been paid to post-communist rural communities, researchers tended to adopt a short-term perspective, focusing mostly on the issue of decollectivization, reconstitution of private ownership over land, and integration into the European market-based agricultural policies. At the same time, historical perspectives on the agrarian question under communism, in general, and the establishment and history of collective farms, in particular, are still scarce. Despite its profound, long-term sociopolitical implications, the collectivization of agriculture in Eastern Europe has remained a relatively underresearched field. In this volume, we posit that, in order to understand the communist and post-communist transformation of Eastern European societies, scholars need to pay attention to the status and evolution of the peasantry and to employ a historical perspective by exploring the comunist agricultural policies and their enduring economic and social implications. 1 To contribute to this analytical effort, the volume explores the interrelated campaigns of agricultural collectivization in the USSR during the interwar and postwar periods and in the communist dictatorships established in the Soviet-dominated Eastern Europe after World War II.